2020
DOI: 10.1101/2020.08.29.20184325
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Face-masking, an acceptable protective measure against COVID-19 - Findings of Ugandan high-risk groups

Abstract: Face-masking could reduce the risk of COVID-19 transmission. We assessed: knowledge, attitudes, perceptions, and practices towards COVID-19 and face-mask use among 644 high risk-individuals in Kampala, Uganda. In data analysis, descriptive, bivariate and multivariate logistic regression analyses, with a 95% confidence interval were considered. Adjusted-odds ratios were used to determine the magnitude of associations. P-values < 0.05 were considered statistically-significant. Majority: 99.7% and 87.3% of the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
(93 reference statements)
2
2
0
1
Order By: Relevance
“…Results suggest that nearly all respondents believe that face masks are effective at preventing COVID-19. These results tend to some extent agree with a recent study in Uganda that shows that a sizeable proportion (68%) of respondents in their study had received information about the use of face masks (29). Our study however, shows a higher percentage of respondents who believe that face masks are effective at preventing COVID-19.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Results suggest that nearly all respondents believe that face masks are effective at preventing COVID-19. These results tend to some extent agree with a recent study in Uganda that shows that a sizeable proportion (68%) of respondents in their study had received information about the use of face masks (29). Our study however, shows a higher percentage of respondents who believe that face masks are effective at preventing COVID-19.…”
Section: Discussionsupporting
confidence: 92%
“…However, these findings also reveal that wearing face masks in public places is not universal ( 25 , 26 ). This is also similar to previous studies that have indicated that a sizeable proportion of the people in low and middle income countries like Nigeria ( 26 ), Ethiopia ( 28 ), Sudan ( 27 ), and Uganda ( 29 ) do not actually always wear masks while leaving home to go to public places.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Ugandoje vyresni nei 64 metų žmonės (89 proc.) buvo mažiau linkę vertinti kaukes teigiamai [19]. Panaši situacija stebima ir Lietuvoje, kur didžioji dalis (55,3%, n=517; p<0,001 ) vyresnių nei 50 metų žmonių teigė, kad kaukės nėra veiksmingos.…”
Section: Tyrimo Rezultatai Ir Jų Aptarimasunclassified
“…A total of 12 studies including meta-analysis, case control, cross sectional, cohort, retrospective, retrospective cross sectional, research, randomized controlled and controlled comparison studies conducted in China, United Kingdom, USA, Thailand, Uganda, Ethiopia, South Korea, Canada, and Iran were reviewed on the protective effect of masks on COVID-19 [39][40][41][42][43][44][45]. All patients had laboratory evidence of SARS-CoV-2.…”
Section: Sars-cov-2 and Masksmentioning
confidence: 99%